2005
DOI: 10.3766/jaaa.16.7.9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Individual Auditory Training in Adults: A Systematic Review of the Evidence

Abstract: A systematic review of the literature was conducted addressing the following question, "Is there evidence of improvement in communication skills through individual auditory training in an adult hearing-impaired population?" Keywords and authors were used as search terms in eight major indexes, and seven textbooks were reviewed for related references. The level of evidence that was accepted included randomized controlled trials, nonrandomized controlled trials, cohort, and before/after designs with or without c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
158
0
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(170 citation statements)
references
References 26 publications
4
158
0
8
Order By: Relevance
“…Recently, Sweetow and Palmer reviewed the capability of perceptual training to improve hearing in patients with SNHL [41]. Several studies of adaptive auditory training have shown performance improvements in subjects with hearing loss [42][43], particularly when visual cues are present [44].…”
Section: Perceptual Training Of Hearing Aid Usersmentioning
confidence: 99%
“…Recently, Sweetow and Palmer reviewed the capability of perceptual training to improve hearing in patients with SNHL [41]. Several studies of adaptive auditory training have shown performance improvements in subjects with hearing loss [42][43], particularly when visual cues are present [44].…”
Section: Perceptual Training Of Hearing Aid Usersmentioning
confidence: 99%
“…Effective rehabilitation interventions are available: Hearing aids (Cox & Alexander, 2002;Kramer, Goverts, Dreschler, Boymans, & Festen, 2002), a group communication program (Hickson, Worrall, & Scarinci, 2006), and an individual communication program (Kramer, Allessie, Dondorp, Zekveld, & Kapteyn, 2005) have yielded overall selfreported outcomes of similar magnitude as measured by the International Outcome Inventory (Hickson et al, 2006). Communication programs are present in large numbers, and their effectiveness has been systematically reviewed (Hawkins, 2005;Sweetow & Palmer, 2005).…”
mentioning
confidence: 99%
“…Neural plasticity is not lost with aging 3,11 . The central auditory nervous system of the elderly is capable of changing and, with hearing training; it is possible to improve speech recognition skills, especially in a noisy background 4 .…”
Section: Discussionmentioning
confidence: 99%